KEADILAN DALAM DIMENSI PLURALITAS HUKUM: TANTANGAN DAN ARAH REFORMASI SISTEM HUKUM INDONESIA - Widharu, Shasa Suta; Sunaryo, Sidik (Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia as a multicultural country faces major challenges in managing legal pluralism that includes state, customary, and religious legal systems. Although the existence of legal plurality is constitutionally recognized, its implementation still shows the dominance of positive law and ignores local and religious legal systems. This inequality hinders the achievement of substantive justice, especially for indigenous communities and minority groups. This study aims to examine the configuration of legal pluralism in Indonesia and formulate an alternative paradigm based on legal pluralism without discrimination within the framework of national legal reform. With a normative-juridical approach, this study highlights the importance of integrating the legal system in a parallel manner and strengthening participatory and community-based conflict resolution mechanisms. The urgency of legal education reform is also emphasized in order to be able to create inclusive and contextual law enforcers. In the context of globalization that encourages the homogenization of law, legal pluralism offers a way to maintain the sustainability of local legal identity. Therefore, legal pluralism without discrimination needs to be mainstreamed in the development of a national legal system that is fair, participatory, and in accordance with the values ​​of Pancasila.